Strategi Dakwah Habib Ja’far Melalui Segmen “Login” di YouTube dalam Meningkatkan Moderasi Beragama - Jeki Bintang Mahendra; Achmad Syarifudin; Muslimin . (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study is entitled "Habib Ja'far's Da'wah Strategy through the Login Segment on YouTube to Increase Religious Moderation." This research is motivated by the importance of religious moderation in a developed society and the rapid development of digital media as a means of da'wah. The Login segment featuring Habib Ja'far is one digital da'wah medium that conveys Islamic values in a moderate, inclusive, and easily accepted manner by the public, especially the younger generation. This study aims to determine Habib Ja'far's da'wah strategy in increasing religious moderation through the Login segment on YouTube. This study uses a descriptive qualitative approach. Primary data was obtained from the Login video segment on YouTube, while secondary data was obtained from books, journals, articles, and other relevant sources. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis utilized data reduction, data presentation, and conclusion drawing. The results show that Habib Ja'far implements a communicative, dialogical, educational, and humanistic da'wah strategy. The preaching is delivered in simple, easy-to-understand language and emphasizes the values of tolerance, respect for differences, and a non-violent stance. Utilizing YouTube as a digital preaching medium can broaden the reach of the message of religious moderation to the public. Supporting factors include the development of digital technology, the public's high interest in religious content, and Habib Ja'far's adaptive communication style. A hindering factor is the audience's differing understanding of the message. Thus, Habib Ja'far's preaching strategy through the Login segment on YouTube is effective in instilling the values of religious moderation and fostering tolerance among the public.